The 2020 China report of the Lancet countdown on health and climate change (2020)
Left unmitigated, climate change poses a catastrophic risk to human health, requiring an urgent and concerted response from every country. As the home to one fifth of the world’s population and the largest emitter of carbon dioxide globally, China’s interventions in climate change are of pivotal importance, both to human health and to the planet. Similar to other countries, climate change mitigation and adaptation would bring immense health benefits for China’s 1·4 billion people, and building these considerations into any COVID-19 recovery strategy and the detailed pathway to fulfil the 2060 carbon neutrality pledge will ensure it improves human wellbeing, both now and in the future. Decisions made over the coming months and years will establish the course of climate change policy for decades to come. To meet this challenge, Tsinghua University (Beijing, China), partnering with University College London (London, UK) and 17 Chinese and international institutions, has produced the Lancet Countdown China report, focusing at the national level and building on the work of the global Lancet Countdown. Drawing on international methods and frameworks, this report aims to understand and track the links between public health and climate change at the national level. This paper is one part of the Lancet Countdown’s broader efforts to develop regional expertise and understanding. Uniquely, the data and results in this report are presented at the provincial level where possible, to facilitate the targeted response strategies for local decision makers.